A case study of a Grade 7 teacher's perspectives and practices related to self-regulated learning (SRL). Issue 2 (14th March 2020) - Alvi, Effat; Gillies, Robyn M.
ABSTRACT: This paper presents an in-depth case study of how a Grade 7 teacher, supported students' self-regulated learning (SRL) by highlighting her perspectives and classroom practices. Under the influence of social cognitive theory, we drew on the self-regulated strategy development (SRSD) model by Harris and Graham to frame the teacher's approach. Data reveal that the teacher emphasized the process of learning, giving a clear vision of goals, in order to support students' SRL. We document the components involved in the teacher's approach which include: developing the context for learning and tuning in, brainstorming, focused and explicit teaching, extending learning, evaluating, and developing advanced cognitive networks for linking understanding and new ideas. We describe these components in detail to be of use to educators and practitioners. We conclude that a teacher may employ different practices to support students' SRL within a real-life classroom.